Schiff Bases: Interesting Scaffolds with Promising Antitumoral Properties - Domenico Iacopetta; Jessica Ceramella; Alessia Catalano; Carmela Saturnino; Maria Grazia Bonomo; Carlo Franchini; Maria Stefania Sinicropi (Applied Sciences, 2021)
Schiff bases, named after Hugo Schiff, are highly reactive organic compounds broadly used as pigments and dyes, catalysts, intermediates in organic synthesis, and polymer stabilizers. Lots of Schiff bases are described in the literature for various biological activities, including antimalarial, antibacterial, antifungal, anti-inflammatory, and antiviral. Schiff bases are also known for their ability to form complexes with several metals. Very often, complexes of Schiff bases with metals and Schiff bases alone have demonstrated interesting antitumor activity. Given the innumerable vastness of data regarding antitumor activity of all these compounds, we focused our attention on mono- and bis-Schiff bases alone as antitumor agents. We will highlight the most significant examples of compounds belonging to this class reported in the literature.